NUMERICAL INVESTIGATION OF A COPPER-WATER NANOFLUID FLOWING IN A PARALLEL PLATE CHANNEL - Ragani, Saeb; Bahrami, Arian (Begell House Inc, 2019)
Heat transfer behavior of a Cu-water nanofluid flowing in a laminar mode in a parallel plate channel was investigated numerically. The governing continuity, momentum, and energy equations were discretized using the finite volume approach and solved with the SIMPLE algorithm. The thermal conductivity of the nanofluid was determined by the model proposed by Patel et al. and the Brinkman model was used to calculate the effective viscosity. The study was conducted for a wide range of Reynolds numbers from 10 to 1500, and for solid volume fractions between 0% and 5%. Top and bottom walls were considered for the cases of constant temperature and constant wall heat flux, while results for both uniform and parabolic entrance velocities were considered for each case. It was observed that the rate of heat transfer increases with increase in solid volume fraction as well as with increase in flow rate. Moreover, higher heat transfer was observed for uniform entrance velocity compared to that of a channel with parabolic inlet velocit
Keywords: nanofluid; rectangular duct; laminar flow; Newtonian fluid